2020
DOI: 10.1590/scielopreprints.819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Access to oral health in primary care before and after the beginning of the COVID-19 pandemic in Brazil

Abstract: This study compared the access to oral health in primary care, before and after the beginning of the COVID-19 pandemic in Brazil. An observational study with a cross-sectional ecological design was carried out, using data from the Health Information System for Primary Care (SISAB). Data regarding the number of Oral Health Teams (OHT), Oral Health Coverage in Primary Care (OHC), number of First Programmatic Dental Consultations (FPDC), and number of visits due to dental abscess and toothache were collected. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
3
0
6
Order By: Relevance
“…Regarding the use of dental services, the demand for adolescent care decreased by approximately 50%, which is in line with the previous literature 7,8 . The recommended social distance due to the pandemic has been shown to significantly impact the demand for dental services, as well as the degree of anxiety experienced by patients 7,21 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the use of dental services, the demand for adolescent care decreased by approximately 50%, which is in line with the previous literature 7,8 . The recommended social distance due to the pandemic has been shown to significantly impact the demand for dental services, as well as the degree of anxiety experienced by patients 7,21 .…”
Section: Discussionsupporting
confidence: 87%
“…Recently published studies have shown changes in the behavioural pattern of individuals subjected to confinement during the COVID‐19 pandemic. The demand and use of dental services showed a reduction of 38% at the beginning of the pandemic, which was also observed in access to primary oral health care in the Brazilian environment 7,8 . Eating habits have undergone somewhat contradictory changes.…”
Section: Introductionmentioning
confidence: 89%
“…Entre 2019 e 2020, houve aumento do número de equipes de saúde bucal em 25 estados e da cobertura em 17 estados, entretanto, comparando-se o primeiro quadrimestre desses dois anos, verificou-se redução significativa no número e cobertura das primeiras consultas odontológicas programáticas e de atendimentos devido a abscesso dento-alveolar e dor de dente (Lucena et al, 2020). Pode-se atribuir essa redução à pandemia tendo em vista a suspensão dos atendimentos eletivos no SUS desde março, diferentes formas de organização dos atendimentos de urgência, bem como de menor acesso e provimento dos EPIs e à própria mudança de comportamento dos usuários na busca pelos serviços (Lucena et al, 2020). Também foi observada uma redução de 65,6% na média de consultas clínicas odontológicas no setor público no Brasil, representando mais de 21 mil consultas clínicas, comparando o período de 2015 a 2019 com o ano de 2020 (Marques et al, 2020).…”
Section: Indicadores Por Estadounclassified
“…Observou-se que o acesso à saúde bucal na atenção básica foi reduzido em 2020, fenômeno que, provavelmente, irá impactar negativamente os dados epidemiológicos de saúde bucal no Brasil (LUCENA et al, 2020).…”
Section: Outro Estudo Desenvolvido Nos Estados Unidos Utilizou a Etnografia Clínicaunclassified